Chad : 2010 Article IV Consultation; Staff Report; Staff Supplements; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report ;, 2010)
Chad's chronic instability has hindered growth and poverty reduction. Chad remains among the poorest countries in the world, and has made little progress toward the Millennium Development Goals. The global financial crisis affected Chad mainly through the decline in oil prices. Prompt reaction to the pressing food shortage needs to be complemented by measures to increase agriculture productivity. The government should adopt a supplementary budget that reduces the non-oil primary deficit while accommodating priority spending. Improving public financial management is the key.